Pengaruh Model Pembelajaran PAIKEM terhadap Keterampilan Berbicara Siswa Kelas IX.5 SMP Negeri 1 Lubuk Basung - Darlizawati (Indra institute Research & Publication, 2023)
This study aims to improve speaking skills for class IX.5 students of SMP Negeri 1 Lubuk Basung through the use of the PAIKEM Learning Model. Based on observations in learning in class IX.5 SMP Ngeri 1 Lubuk Basung shows that in the process of learning Indonesian, it seems that students are not skilled at speaking (poor fluency, feel embarrassed and afraid). Students look stiff in speaking in front of the class and the choice of words used is not varied. This research is a class action research (Classroom Action Research) conducted in two cycles. The data obtained in the study were analyzed using qualitative and quantitative data analysis. The results of this study indicate that the use of the PAIKEM learning model that was implemented in this study proved to be very effective and efficient in improving the speaking skills of class IX.5 students of SMP Negeri 1 Lubuk Basung. From the research analysis, students' ability to convey criticism of works of art/products by paying attention to pronunciation, intonation, expression, and language, as well as fluence increased. Therefore, learning by applying the PAIKEM model is proven to be able to improve students' speaking skills.